Pengembangan Media Pembelajaran Interaktif Berbasis Web Game Wordwall pada Materi Pengaruh Gaya terhadap Benda Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - Khairunnisaa', Nabilla; Astimar, Nelly (ARZUSIN, 2024)
This study was motivated by the lack of use of digital technology-based media in IPAS learning, especially in the material of the effect of force on objects. In the results of observations and interviews it was found that students' interest in learning was very high by using digital-based learning media, so the development of digital-based interactive learning media was needed. This research aims to develop interactive learning media based on the Wordwall web game using the Problem Based model that is valid, practical, and effective. This media development uses the ADDIE model, which consists of several stages, namely: analysis, design, development, implementation, and evaluation. The research was conducted in class IV SDN 05 Tarok Dipo with 20 students. The results of the material expert validity test on learning media obtained a percentage of 89% with a very valid category, the results of the language expert validity test obtained a percentage of 97% with a very valid category, and the results of the media expert validity test obtained a percentage of 78% with a valid category. The results of the teacher response practicality test obtained a percentage of 96% with a very practical category. The results of the student response practicality test obtained a percentage of 92.5% with a very practical category. The results of the effectiveness test obtained a pre-test with a result of 67% and a post-test of 85%, this shows an increase in learning outcomes. So it can be concluded that the interactive learning media based on the Wordwall web game on the material of the effect of force on objects using the problem-based learning model in grade IV elementary school is declared valid, practical, and effective.